Video Media In Learning Islamic Religion Education - Ahmad Syafi'i (Yayasan Sinergi Kawula Muda, 2023)
Media in Islamic Studies serves to streamline and streamline learning. This paper describes the perspective of video media, types, syntax, characteristics, benefits, and advantages and disadvantages. This paper is a literature research using a content analysis model. The results of this study show that: 1) video is a combined tool of audio and visual media used simultaneously in learning. 2) Types of videos i.e. DVD, computer video, internet video, and streaming video. 3) The syntax of using video media, namely the preparation stage includes checking tools, understanding the relevance of video material and content, directing students to provide stationery. The implementation stage includes designing seating patterns, conveying goals, presenting tasks, presenting videos, monitoring student work, providing opportunities for students to be actively involved in dialogue, ensuring students understand the video, and students doing assignments. 4) Video characteristics are clarity of message, stand-alone, friendly, content representation, visual, and classical as well as individual. 5) The benefits of video are to streamline and streamline learning. 6) Excellence: awaken students' imagination, students learn actively, material is delivered to a large number of students, and encourages students. Weaknesses: the creativity of gur is limited, difficult to present if students cannot think abstractly, and requires special tools in delivery.